One system of differential equations in partial derivatives of the second order - Tasmambetov , Zh. N. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Particular cases of a special system of partial differential equations whose solutions are representable in the form of special functions and orthogonal polynomials in two variables are studied.